A study on ethnomedicinal plants of Kalavai, Vellore District, Tamil Nadu, India - A. Natarajan, K.S. Leelavinodh, A. Jayavelu, K. Devi, B. Senthil Kumar (Journal of Applied Pharmaceutical Science, 2013)
A qualitative ethanobotanical survey was carried out among the local Irula tribals of Kalavai village, Vellore district, Tamil Nadu, to study the various medicinal plants that are used by the people for the treatment of common ailments such as fever, cold, cough, diabetes, jaundice, diarrhea, rheumatism, snake bite, and headache, in order to evaluate the potential medicinal uses of local plants. 250 respondents were interviewed. A total of 50 species of plants used by the local tribes of Kalavai are described in this study based on questionnaire, interviews and discussions with the local people. Several plants were found to be effective in curing asthma, skin disease, headache, wound healing, cough, cancer, fever, cold, rheumatism, hepatitis, diarrhea, paralysis, dyspepsia, ulcers, dysentery, tumors, some viral infections and scorpion bite. Conservation and cultivation of these plants is essential for sustaing the medicinal and cultural resource of mankind.
Keywords: Folklore medicinal plants, Fruit plants, Ornamental